Synergy Analysis of Social Intermediation of Sharia Banking KC Kabanjahe and Local Economic Development (LED) in Supporting the Welfare of the Communities of Nari Gunung Village II - Dicky Aris Munanda Meliala; Imsar Imsar; Juliana Nasution (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to synergize Sharia banking social intermediation and Local Economic Development (LED) in supporting the welfare of citrus farming communities, to determine the role and policies of Indonesian Sharia Banks in the welfare of farmer group communities in Nari Gunung II Village, Tiganderket District, Karo Regency. This type of research is qualitative research. The results of this study, namely, the social intermediation of Islamic banking through the distribution of capital to develop community citrus farming businesses obtained good results. Bank Syariah Indonesia Kc Kabanjahe participates in helping citrus farming communities by providing capital for a maximum term of 5 years. Islamic banks also provide policies to citrus farming communities. These policies include channeling funds to the public through soft financing, and praying for customers to always be trustworthy in managing the financing provided. In addition, the results of the questionnaire filled out by the orange farmer group in Nari Gunung II Village, Tiganderket District, Karo Regency obtained an average of 168.33. This shows that the life of the orange farmer group community is increasing and prosperous.